Clinical Practice Guide for Anaphylaxis in Latin America (Galaxia-Latam) - Victoria Cardona; Alberto Álvarez-Perea; Ignacio Javier Ansotegui-Zubeldia; Alfredo Arias-Cruz; Juan Carlos Ivancevich; Sandra Nora González-Díaz; Patricia Latour-Staffeld; Mario Sánchez-Borges; Carlos Serrano; Dirceu Solé; Luciana Tanno; Nieves Cabañes-Higuero; et al. (Revista Alergia México, 2019)
Anaphylaxis is a severe allergic reaction with a rapid onset and it is potentially life-threatening. Its clinical manifestations are varied; they may affect the skin, the cardiovascular system, the respiratory system, and the digestive system, among others. The treatment of choice, which is an intra-muscular injection of epinephrine (adrenaline), must be applied promptly. Therefore, being prepared to recognize it properly is of crucial importance. The objective of this clinical practice guide is to improve the knowledge of health professionals about anaphylaxis and, consequently, to optimize the treatment and long-term management of this reaction. This guide is adapted to the peculiarities of Latin America; especially in matters regarding the treatment. The need to introduce epinephrine auto-injectors in countries that don’t have them yet is highlighted.